Comprehensive studies on postpartum uterine infections in dystocia affected cows and buffaloes - SINGH, BHAJAN; NANDA, A S; ARORA, A K (The Indian Journal of Animal Sciences, 2013)
Bacteriological studies conducted on the uterine discharge samples collected from dystocia affected buffaloes (n:30) and cows(n:20) revealed that high proportion of bacteria were isolated immediately before and after the assisted calvings. The infections persisted longer in dystocia affected animals. The organisms isolated were Escherichia coli, Staphylococci, Actinomyces pyogenes, Streptococci, Proteus spp, Bacillus spp., Pseudomonas aeruginosa and Klebsiella spp. By the day 35, uterine infections were cleared in higher proportion of dystocia affected cows compared to buffaloes.